Comparative evaluation of microleakage among Resin-Based and nonResin-Based Restorative Materials in dentine cavities - Simone Thiedig; Maria Giraki; Stefan Rüttermann; Susanne Gerhardt-Szep (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
The aim of this randomized in vitro study is to clarify whether resin based restorative materials (RBRM) behave in a way comparable to non-resin based restorative materials (non-RBRM) in dentine-limited cavities with regard to their marginal fit. For this purpose, cylindrical standardized cavities (diameter: 3.0 +/- 0.1 mm, depth: 1.5 mm) were placed on buccal surfaces of sixty human molars and restored with three non-RBRM (glass ionomer cement, amalgam, phosphate cement) and three adhesive (composite, compomer, ormocer) restoratives. Aging of the samples was achieved by thermal cycling (500 cycles). The marginal gaps could be made visible with a dye penetration test (methylene blue 2%). Using a diamond internal hole saw, 5 cuts were made through the cavity and measured under an incident light microscope at 10x magnification. The result of the statistical evaluation of the additionally determined percentage marginal gap depths was compared with the numerical evaluation of the penetration depths of 0, 1 and 2 required by the ISO test setup. The ISO classification reveals statistical differences in the penetration behaviour of phosphate cement to the other materials, whereas the statistical evaluation of the percentage measurement distances revealed significant differences between the nonadhesive and the adhesive restorative materials, with significantly smaller marginal gaps for the cavities of the RBRM group.